GE_GERICHTE C/20485/2014 vom 17. Oktober 2016 - GE Cour de justice (2016)
BAIL À LOYER; LOCAL PROFESSIONNEL; PRINCIPE DE LA BONNE FOI; RÉSILIATION; CONGÉ DE REPRÉSAILLES | CO.272a.1.a; CPC.59.1; CO.257f; CO.271.1; CO.263